Serious game in introductory psychology for professional awareness: Optimal learner control and authenticity. (29th May 2020) - Hummel, Hans G. K.; Nadolski, Rob J.; Eshuis, Jannes; Slootmaker, Aad; Storm, Jeroen
Abstract: Introductory Psychology courses in Higher Education lack application of knowledge in solving work‐based problems. We develop and study mini‐games that support a more active and experiential way of learning to increase professional awareness. This paper describes the instructional design and the factors under study: learner control and authenticity. We compared professional awareness and perceived authenticity for the old (without game, n  = 130) and new course (with game, n  = 197) by administering pre‐ and post‐questionnaires. Participants were allocated to game variants, differing in freedom of assignment order (less or more learner control) and number of sources available (less or more authentic). We computer logged their game actions, and asked them additional questions about gameplay that concerned aspects like motivation, flow, performance, learnability and usability. Both courses improved professional awareness (knowledge gains of 4% for the old and 12% for the new course), but only in the new course with mini‐games this was significant. Students evaluated gameplay and their content as "more than sufficient" to "good." A free order of assignments was found to produce more effective (in‐game) performance, and the provision of more sources was found to improve learnability, authentic learning and appreciations of gameplay.